Fish and Sun - Ruzzier, Sergio, 1966- (I can read comics!., 2021)
One day, bored little Fish journeys up to the surface of the ocean where it meets Sun, and a wonderful friendship blooms... Only, right in the middle of their fun, Sun starts to set!